Komunikacija s pacientom v večjezični družbi - Morel, Alenka (visokošolska dela, 2009)
Interpreting in health care in Slovenia reflects insufficient legal basis that would organise it in an integrated way and enable its further development. The current state of play of health care interpreting is managed through improvisation and goodwill of all parties involved. As a type of community interpreting, health care interpreting is substantiated by the growing number of people in Slovenia unfamiliar with the language. Patients with problems in communication as a rule do not report infringements to public services. Doctors get help from ad-hoc rather than professional interpreters and, confronted with interlingual or intercultural relations and not being especially prepared, improvise. Similarly, interpreters depend on themselves, having received no appropriate training and practicing in their free time. Integrated arrangement of interpreting in health care is necessary, offering the patient information, providing the doctor with guidelines for working with interpreters, and giving the interpreters standards of practice and systematised professional qualifications and working status.
Keywords: community interpreting; prevajanje za skupnost; interpretation; interpreting; tolmačenje; terminologija; terminology; health-care; zdravstveno varstvo; zdravstvo; health care; Slovenia; Slovenija; medicine; medicina; communication; komunikacija; patient; pacient; magistrska dela